2019
DOI: 10.1097/spv.0000000000000665
|View full text |Cite
|
Sign up to set email alerts
|

All Levels of Providers Can Effectively and Efficiently Teach Pelvic Floor Strength Assessment at Time of Pelvic Examination

Abstract: Objective In women who undergo provider-guided vaginal biofeedback of pelvic floor muscle strength, we sought to determine whether the level of the provider correlates with the patient’s ability to achieve adequate pelvic floor muscle contractions (PFMCs). Methods From August 2017 to April 2018, patients from 2 urogynecology clinics were recruited to participate in an institutional review board–approved, prospective study examining PFMCs. Pelvic examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Indeed, some studies have shown that females were either unable or had difficulty performing correct deep pelvic floor musculature contraction during the assessment. 19 The heatmaps revealed comparable results for the EAS and the PRM at the item level for "voluntary relaxation," "tone," and "maximum voluntary contraction." The literature reveals no strict consensus about the relationship between the EAS and the PRM, though several studies have found connections between the two muscles.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Indeed, some studies have shown that females were either unable or had difficulty performing correct deep pelvic floor musculature contraction during the assessment. 19 The heatmaps revealed comparable results for the EAS and the PRM at the item level for "voluntary relaxation," "tone," and "maximum voluntary contraction." The literature reveals no strict consensus about the relationship between the EAS and the PRM, though several studies have found connections between the two muscles.…”
Section: Discussionmentioning
confidence: 85%
“…The difference in function between muscles could be explained by the difficulty to contract the PRM due to its location within the pelvis. Indeed, some studies have shown that females were either unable or had difficulty performing correct deep pelvic floor musculature contraction during the assessment 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that patient teaching of pelvic floor exercises led by OB/GYN specialists may serve as a cost-effective, low-resource tool to improve patient symptoms of pelvic floor dysfunction. 63 …”
Section: Introductionmentioning
confidence: 99%